2023
DOI: 10.11152/mu-3594
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasonography for the confirmation of endotracheal tube intubation: a systematic review and meta-analysis

Abstract: Aim: Despite several studies and reviews reporting data accuracy of ultrasonography for confirmation of endotracheal intubation, there has been limited pooled evidence summarizing the diagnostic accuracy of this imaging modality, especially based on recent evidence. Hence, the current study reviews the recent literature and conducts a meta-analysis to compare the accuracy of ultrasonography for the confirmation of endotracheal tube placement.Material and methods: We conducted a systematic search for all studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The tube must be adjusted according to the patient's dimensions and carefully secured at the proper distance at the incisors. Additional checks that are essential by the anesthetist to find out malplacement of an endotracheal tube include observation for symmetrical chest movements (rise and fall during positive pressure ventilation, indicating proper inflation of both lungs), colorimetric capnography (it measures the concentration of carbon dioxide in exhaled air), video laryngoscopy and fiberoptic bronchoscopy (direct visualization of the tube passing through the vocal cords), use of depth markers, and ultrasonography (used to visualize the trachea and confirm endotracheal tube placement, particularly in challenging cases or when other methods are inconclusive) [6][7][8]. Furthermore, the surgeon should consistently monitor the movements of the pleura on both sides, which are influenced by the inflation and deflation of the lungs following mid-sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The tube must be adjusted according to the patient's dimensions and carefully secured at the proper distance at the incisors. Additional checks that are essential by the anesthetist to find out malplacement of an endotracheal tube include observation for symmetrical chest movements (rise and fall during positive pressure ventilation, indicating proper inflation of both lungs), colorimetric capnography (it measures the concentration of carbon dioxide in exhaled air), video laryngoscopy and fiberoptic bronchoscopy (direct visualization of the tube passing through the vocal cords), use of depth markers, and ultrasonography (used to visualize the trachea and confirm endotracheal tube placement, particularly in challenging cases or when other methods are inconclusive) [6][7][8]. Furthermore, the surgeon should consistently monitor the movements of the pleura on both sides, which are influenced by the inflation and deflation of the lungs following mid-sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have demonstrated that ultrasound has high diagnostic value. [69][70][71][72][73] A 2018 meta-analysis of 17 studies found an overall 98.7% sensitivity, 97.1% specificity, a positive likelihood ratio of 34.4, and a negative likelihood ratio of 0.01. Importantly, "subgroup analyses did not demonstrate a significant difference by location, provider specialty, provider experience, transducer type, or technique".…”
Section: Airway Pocusmentioning
confidence: 99%
“…The question remains, how reliable is ultrasound to detect successful versus unsuccessful endotracheal intubation? Several meta-analyses have demonstrated that ultrasound has high diagnostic value 69–73 . A 2018 meta-analysis of 17 studies found an overall 98.7% sensitivity, 97.1% specificity, a positive likelihood ratio of 34.4, and a negative likelihood ratio of 0.01.…”
Section: Point-of-care-ultrasoundmentioning
confidence: 99%